2020
DOI: 10.1080/13685538.2020.1768367
|View full text |Cite
|
Sign up to set email alerts
|

Can myocardial performance index predict early cardiac risks in erectile dysfunction?

Abstract: Aim: Myocardial performance index (MPI) is an easy-to-apply and non-invasive method that shows both systolic and diastolic functions of the heart. In this study, it was aimed to evaluate the relationship between erectile dysfunction (ED) and MPI. Methods: The study included 45 male patients admitted to the urology outpatient clinic for ED and 48 healthy male volunteers. Echocardiographic evaluation of all participants was performed. Isovolumetric contraction time (IVCT), isovolumetric relaxation time (IVRT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Although Bardazzi et al [16] associated ED especially with patients with mild psoriasis, it was observed in our study that the incidence and severity of ED increased as PASI increased (psoriasis progressed). Ji et al reported that investigating erectile function can help assess cardiovascular status and determine the increased risk of cardiovascular events in patients with plaque psoriasis [17,18]. In psoriasis patients, sexual health problems should be examined in detail both to diagnose cardiovascular diseases early and to increase their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Although Bardazzi et al [16] associated ED especially with patients with mild psoriasis, it was observed in our study that the incidence and severity of ED increased as PASI increased (psoriasis progressed). Ji et al reported that investigating erectile function can help assess cardiovascular status and determine the increased risk of cardiovascular events in patients with plaque psoriasis [17,18]. In psoriasis patients, sexual health problems should be examined in detail both to diagnose cardiovascular diseases early and to increase their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk cannot be attributed only to conventional cardiovascular risk factors, such as advanced age, smoking, hypertension (HTN), hyperlipidemia, and diabetes mellitus (DM). Other risk factors such as inflammation, hypervolemia, malnutrition, anemia, secondary hyperparathyroidism (SHPT), oxidative stress, and bone mineral disorders also play a role in CKD patients [2][3][4][5] . Left ventricular hypertrophy (LVH) and left ventricular mass index (LVMI) are independent predictors of cardiovascular mortality in CKD patients [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%